A Comparison between Greek and Danish Citizens' Perceptions of the Nursing Uniform and the Impact on Patients’ Health - Nick, Bakalis; Fabiola, Skenterai; Maria, Spyropoulou; Theonimfi, Fasoulaki; Eleni, Michalopoulos; Giorgios, Vlachopoulos; Panagiotis, Anagnostou; Nikolaos, Filiotis (International Journal of Innovative Research in Medical Science, 2022)
Background & Objectives: Since the 1800s, when nursing attire appeared, it has undergone many changes to offer greater practicality and flexibility during nursing tasks. The study aims to identify and compare Greek and Danish citizens perceptions of the nursing uniform and the impact it may have on patients’ health. Methods: A questionnaire was designed with a total of 33 items. Convenience sampling was used. The total sample (n=1008) included Greek (nG=469) and Danish citizens (nD=539). Results were analysed using the statistical program SPSS24. Results: The white nursing uniform prevalent in current hospitals does not negatively affect patient's health (p<0.05), and specifically does not cause patients symptoms such as anxiety (p<0.05), fear (p<0.05), increased heart rate (p<0.05), tendency to faint (p<0.05), sweating (p<0.05), shortness of breath (p<0.05) and panic attacks (p<0.05). Conclusions: A large percentage of citizens believe that nursing attire should differ in clinics that accommodate children and patients with mental illnesses.